Radius' Giant Cell Tumor: Allograft with Conservation of Distal Radioulnar Joint - Ruatti, S.; Boudissa, M.; Grobost, P.; Kerschbaumer, G.; Tonetti, J. (Journal of Wrist Surgery, 2019)
Purpose Giant cell tumor of the distal radius are frequent lesions, and different types of surgeries have been described. Functional results, after conservative treatment or arthrodesis, often find a decreased strength and range of motion. The sacrifice of the distal radioulnar joint could be one of the causes. We report the case of a 26-year-old patient who presented with a Campanacci Grade III giant cell tumor of the distal radius. We managed his case by the association of en bloc resection and allograft reconstruction with the preservation of distal radioulnar joint.Hypothesis This procedure could improve functional results, without increasing the risk of recurrence at 2 years follow-up.Case Report The originality of our technique was the possibility of distal radioulnar joint conservation. We preserved a long portion of cortex bone all through the ulnar side of the distal radius. We then used an allograft of distal radius, fixed by a reconstruction anatomical plate.Results At 2 years follow-up, the range of motion was 100° with 60° of palmar flexion, 40° of extension, 75° of pronation, and 70° of supination. Radial and ulnar inclination were 10 and 15°, respectively. MTS (Musculoskeletal Tumor Society Score) 1993 was 88% and DASH score was 6. Concerning grip strength, it was measured at 85% in comparison with the other side. Pronation and supination strengths were 80 and 73%, respectively, in comparison with the other side. At follow-up, standard X-rays showed no recurrence. The allograft was well integrated.Conclusion Conservative treatment of the distal radioulnar joint allowed an almost ad integrum recovery, concerning strengths and range of motion. It allows a better functional recovery, without increasing the risk of recurrence.
Keywords: giant cell tumor; en bloc resection; allograft; distal radioulnar joint